2017
DOI: 10.1093/humrep/dex036
|View full text |Cite
|
Sign up to set email alerts
|

Clustering of PCOS-like traits in naturally hyperandrogenic female rhesus monkeys

Abstract: Funded by competitive supplement to P51 OD011106 (PI: Mallick), by P50 HD028934 (PI: Marshall) and by P50 HD044405 (PI: Dunaif). The authors have no potential conflicts of interest.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(49 citation statements)
references
References 125 publications
(134 reference statements)
3
45
0
1
Order By: Relevance
“…Modified from [11], with late gestation T-exposed data modified from [12]. a Phenotypes: type A, hyperandrogenism or hirsutism (Women only) (HA) + intermittent/absent cycles (OD) + polycystic ovary morphology or circulating AMH level ≥ 10 ng/mL (PCOM); type B, HA + OD; type C, HA + PCOM; type D, OD + PCOM, as described [13].…”
Section: -----------67%-----------mentioning
confidence: 99%
See 1 more Smart Citation
“…Modified from [11], with late gestation T-exposed data modified from [12]. a Phenotypes: type A, hyperandrogenism or hirsutism (Women only) (HA) + intermittent/absent cycles (OD) + polycystic ovary morphology or circulating AMH level ≥ 10 ng/mL (PCOM); type B, HA + OD; type C, HA + PCOM; type D, OD + PCOM, as described [13].…”
Section: -----------67%-----------mentioning
confidence: 99%
“…Such etiopathogenic mechanism(s) also include the non-hyperandrogenic adult PCOS phenotype (type D), which shares gene variant associations with hyperandrogenic phenotypes [28]. Moreover, gestational T excess produces female macaque offspring that exhibit both hyperandrogenic and non-hyperandrogenic adult phenotypes [12], while hyperandrogneic and non-hyperandrogenic PCOS-related phenotypes also occur naturally in female macaques [13].…”
Section: Pcos and Its Potential Originsmentioning
confidence: 99%
“…In female rodents and sheep, for example, fetal T commonly abolishes maturation of ovarian E 2 -induced GnRH/LH surges in adulthood, preventing ovulation [51,85]. In contrast, adult female monkeys exposed to naturally occurring [36] or experimentally induced [33,61] fetal T excess retain the ability to demonstrate ovarian E 2 -induced LH (and likely GnRH) surges and ovulatory menstrual cycles. Women with PCOS [86], and with known exposure to fetal T excess [87], also demonstrate E 2 -induced LH surges or ovulatory menstrual cycles.…”
Section: Discussionmentioning
confidence: 99%
“…Emulating LH traits in women with PCOS, elevated LH levels in PA monkeys show resistance to negative feedback suppression from either exogenous estradiol [33] or gonadotropin hyperstimulated, endogenous ovarian hormone release [34]. In a separate study, adult female rhesus monkeys with naturally occurring hyperandrogenism also exhibit elevated LH levels and accompanying PCOS-like reproductive dysfunction [35,36], together with genital biomarkers indicative of fetal T excess [36]. Numerous studies have since demonstrated fetal T or dihydrotestosterone (DHT) programming of LH hypersecretion as a consequence of elevated episodic release of GnRH/LH in PA adult female sheep [37][38][39], rats [40,41], and mice [42,43].…”
Section: Introductionmentioning
confidence: 93%
“…Table 1 Example of diseases and traits reported in rhesus macaques. Diseases are grouped based on whether a genetic association has been reported in macaques for that disease Genetic Association Reported SIV progression [1][2][3] Age-related macular degeneration [4,5] Colorectal cancer [6] Krabbe disease [7] Ammenorhea [8] Naltrexone response [9] HPA axis dysregulation [10] Alcohol intake levels [11][12][13] Anxiety [14,15] No Genetic Association Reported Autism [16] Age-associated coginitive decline [17] Polycystic ovary syndrome (PCOS) [18] Endometriosis [19][20][21] Left ventricular hypertrophy [22] Type III Von-Willebrand [23] Type II Diabetes [24][25][26] Squamous cell carcinoma [27] Coat-like retinopathy [28] TB progression [29] Osteoporosis [30]…”
Section: Introductionmentioning
confidence: 99%